1999
DOI: 10.1002/(sici)1098-2825(1999)13:6<291::aid-jcla7>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

p27 cell‐cycle inhibitor is inversely correlated with lymph node metastases in right‐sided colon cancer

Abstract: p27, a cyclin-dependent kinase inhibitor, suppresses proliferation of normal and neoplastic cells. Expression of p27 is correlated with survival in colon cancer. To some degree, right-sided colon cancers differ biologically and clinically from left-sided colon cancers. We analyzed 41 patients with right-sided colon cancers, including 18 cases with regional lymph node metastases and 23 cases with negative lymph nodes. Immunostaining for p27 was performed on histologic sections of primary cancers and scored. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…A previous study showed an inverse association between PI3K/mTOR activation and p27 expression, and targeting this pathway promoted the expression of p27 [45]. The down-regulation of mTORC1 dephosphorylates 4E-BP1, followed by its binding to eIF4E, which blocks protein translation and cell proliferation [42,43]. The findings from the present study showed upregulation of p27 and down-regulation of p-S6 in SW1736 and BHP7-13 cells treated with PL-Pt(II).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A previous study showed an inverse association between PI3K/mTOR activation and p27 expression, and targeting this pathway promoted the expression of p27 [45]. The down-regulation of mTORC1 dephosphorylates 4E-BP1, followed by its binding to eIF4E, which blocks protein translation and cell proliferation [42,43]. The findings from the present study showed upregulation of p27 and down-regulation of p-S6 in SW1736 and BHP7-13 cells treated with PL-Pt(II).…”
Section: Discussionsupporting
confidence: 61%
“…These findings supported the anti-proliferative activity of PL-Pt(II) for thyroid cancer cells by targeting the PI3K/ mTOR pathway. The activation of mTORC1 induces expression of S6 ribosomal protein, which is a downstream component of the S6 kinase 1 [41][42][43]. The p-S6 protein phosphorylation promotes the translation of proteins that increase the growth of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of p27 KIP1 in colon tumor progression has been revealed in mice carrying the heterozygous or homozygous ablations of the p27 KIP1 gene (Moser et al, 1990; Fero et al, 1996; Philipp‐Staheli et al, 2002; Yang et al, 2003). Moreover, downregulation of p27 KIP1 protein levels or its altered subcellular location is becoming a reliable prognostic predictor for advanced disease and poor patient survival in colorectal carcinoma (Liu et al, 1999; Sgambato et al, 1999; Hoos et al, 2002; Li et al, 2002; Hershko and Shapira, 2006, and references therein). Therefore, loss of p27 KIP1 function appears to play a major role during tumor progression.…”
Section: Discussionmentioning
confidence: 99%